Curve benders : how strategic relationships can power your non-linear growth in the future of work - Nour, David, 1968- (John Wiley & Sons, Inc., 2021)
"Curve Benders is a personal growth roadmap at the intersection of the future of how we'll work, live, play, give, and our strategic relationships. The book will focus how strategic relationships can dramatically alter our growth trajectory in both its direction and ultimate destination against the forces that will shape the future of how we'll work, live, play, and serve others. The author's research has identified 15 forces which will heavily influence what we'll be doing, and how and where we'll engage our current and prospective relationships to create value and make a difference in the lives of others. To remain relevant, we'll need to upskill, reskill, and redeploy our knowledge, skills, and behaviors. None of us can predict the future. We can all plan our strategic path forward. The goal of Nour's research, interviews, and this book is to provide the reader with a roadmap for personal, professional, and organizational growth. Beyond a linear growth journey, the author highlights how certain relationships enable a non-linear growth trajectory. Beyond what we can accomplish, they often shape who we become. The relationships are "curve benders" and Nour describes who and where they are, how to find and engage them, and equally valuable, how one becomes a curve bender to profoundly impact the lives and livelihoods of others"--